Blind tiger eaudiobook - Brown, Sandra (2021)
From a New York Times bestselling author, a war-weary soldier jumps from a moving freight train to avoid trouble–and lands in more than he bargained for. On the day Thatcher Hutton arrives in Foley, Texas, a local woman goes missing. Thatcher becomes the prime suspect. Standing between him and exoneration are a corrupt mayor, a crooked sheriff, and a young widow named Laurel Plummer. As violence erupts, Thatcher and Laurel find themselves on opposite sides of a moonshine war, where blood flows as freely as whiskey. Includes a Reading Group Guide.